Concomitant changes in radiation resistance and trehalose levels during life stages of Drosophila melanogaster suggest radio-protective function of trehalose. (16th April 2018) - Paithankar, Jagdish Gopal; Raghu, Shamprasad Varija; Patil, Rajashekhar K.
Abstract: Purpose: During development, various life stages of Drosophila melanogaster ( D . melanogaster ) show different levels of resistance to gamma irradiation, with the early pupal stage being the most radiation sensitive. This provides us an opportunity to explore the biochemical basis of such variations. The present study was carried out to understand the mechanisms underlying radiation resistance during life stages of D . melanogaster . Materials and methods: Homogenates from all the life stages of D . melanogaster were prepared at stipulated age. These homogenates were used for the determination of (1) enzymatic antioxidants: superoxide dismutase (SOD), catalase, D . melanogaster glutathione peroxidase ( Dm GPx), and glutathione S-transferase (GST); (2) reducing non-enzymatic antioxidants: total antioxidant capacity (TAC), reduced glutathione (GSH) and non-reducing non-enzymatic antioxidant trehalose; and (3) levels of protein carbonyl (PC) content. Age-dependent changes in radiation resistance and associated biochemical changes were also studied in young (2 d) and old (20 and 30 d) flies. Results: TAC and GSH were found high in the early pupal stage, whereas catalase and Dm GPx were found to increase in the early pupal stage. The non-feeding third instar (NFTI) larvae were found to have high levels of SOD and GST, besides NFTI larvae showed high levels of trehalose. A remarkable decrease was observed in radiation resistance and trehalose levels during the early pupal stage. The PC level was the highest during early pupal stage and was the lowest in NFTI larvae. Older flies showed high level of PC compared with young flies. Conclusion: In vitro increments in trehalose concentration correspond to reduced formation of PCs, suggesting a protective role of trehalose against free radicals. A strong correlation between levels of trehalose and PC formation suggests amelioration of proteome damage due to ionizing radiation (IR). Stages with high trehalose levels showed protected proteome and high radiation resistance, suggesting a significant role for this disaccharide in radiation resistance.